A7.17 Effects of baricitinib on multibiomarker disease activity scores and their components in a phase 2b study in moderate-to-severe rheumatoid arthritis patients. (24th February 2016) - Taylor, PC; Genovese, MC; Keystone, E; Weinblatt, M; Rancourt, J; Nantz, E; Schlichting, DE; Zuckerman, SH; Macias, WL
Abstract : Background and objectives: Baricitinib, an oral inhibitor of JAK1 and JAK2 signalling, improved signs and symptoms in patients with active rheumatoid arthritis (RA) who were methotrexate inadequate responders (MTX-IR) in a double-blind, placebo (PBO) controlled study. We investigated how a quantitative, multibiomarker disease activity score (MBDA) and its components are affected by treatment with baricitinib 4mg (n = 50) once daily compared to PBO (n = 79) during 12 weeks' treatment in moderate-to-severe RA patients. Materials and methods: Serum samples were collected at baseline and Weeks 4 and 12. MBDA scores and changes in individual MBDA components were subjected to post-hoc statistical analyses. Results: At baseline, the proportion of patients with low, moderate, and high MBDA scores were similar in the 2 groups, as were median MBDA scores (PBO=44 vs. baricitinib=47). Unlike PBO-treated patients, baricitinib patients had decreased MBDA scores at 4 and 12 weeks compared to baseline (baricitinib=35.5 and 37.0 (p < 0.001) vs. PBO=46.0 and 45.0, respectively). Baricitinib-treated patients had significant (p < 0.05) median % decreases in MBDA components vs. PBO including C-Reactive Protein (-66.9 vs. 6.6/-56.1 vs. 8.2 at 4/12 weeks), Matrix metalloproteinase (MMP)-3 (-12.3 vs. 4.5/-14.5 vs. 6.3 at 4/12 weeks), serum amyloid A (-56.4 vs. 9.9/-37.6 vs. 9.2 at 4/12 weeks), soluble TNF receptor (-12.1 vs. -0.1/-12.0 vs. 1.2 at 4/12 weeks), VCAM-1 (-15.9 vs. 1.4/-12.1 vs. 1.0 at 4/12 weeks), and human cartilage glycoprotein 39; -26.2 vs. -0.5/-9.9 vs. -1.6 at 4/12 weeks). Compared to PBO, there were no significant changes for baricitinib-treated patients at either timepoint for epidermal growth factor (EGF), MMP-1, or vascular endothelial growth factor-A. For baricitinib-treated patients versus PBO, at 4 but not 12 weeks, Interleukin-6 and resistin were significantly decreased and at 12 but not 4 weeks, leptin was significantly increased. Conclusions: Consistent with other indices of disease activity, the treatment of MTX-IR patients with baricitinib 4mg once daily resulted in a reduction in MBDA scores, by 4 weeks. Decreases in MBDA scores and the components were present at both 4 and 12 weeks. Reduction in the levels of inflammatory markers beyond those associated with an acute phase response is apparent in these patients.